Optimization of GaInP solar cell performances - Benaicha, M.; Ounissi, A. (Science des matériaux (Laboratoire LARHYSS), 2016)
In this paper we study a BSF layer structure of a GaInP solar cell and we search for technological parameters of this last leading to its optimized performance (using PC1D simulator). The optimized structure gives the following results: η=19% and FF=85,2%. We also compare these cell performances with those of an optimized GaInP single junction solar cell to show the BSF layer improvement.